A democratic dénouement? The European Union vs terrorist content online | Um desfecho democrático? A União Europeia vs conteúdo terrorista online - Robinson, Gavin (Revista Publicum, 2019)
Abstract: This paper explores the manifold aspects of the draft Terrorist Content Online (‘TCO’) Regulation which are of clear import for the democratic future of the internet insofar as they will reshape the boundaries of what is acceptable behavior online and set out tools and procedures for deciding what must be (potentially, pre-emptively) excised from the exchanges taking place there. The piece places particular emphasis on the proposal’s ramifications for legal certainty and freedom of expression in cyberspace. In doing so, it aims to raise the most salient policy concerns, legal difficulties and technological quandaries which ripple out from the EU legislator’s laudable goal of tackling violent and terrorist content online. The article is structured as follows: after a discussion of the foundational concept of “terrorist content” which applies across the board in the draft text (II), we distinguish its headline provisions tightening up service providers’ compliance with orders to remove or disable access to terrorist content (III) from those aspects of the proposal which aim to responsibilise providers to act unassisted against terrorist content, including through the hotly-debated use of proactive measures (IV). A few concluding remarks on the future direction of this live file are offered to close (V). Resumo: Este artigo explora os múltiplos aspectos do projeto de Regulamento de Conteúdo Terrorista Online (’TCO’), que são de clara importância para o futuro democrático da Internet, na medida em que reformularão os limites do comportamento aceitável online e definirão ferramentas e procedimentos para decidir o que deve ser (potencialmente, preventivamente) excluído das trocas que ocorrem ali. O estudo coloca ênfase particular nas implicações da proposta para segurança jurídica e liberdade de expressão no ciberespaço. Ao fazê-lo, visa levantar as mais importantes preocupações políticas, dificuldades jurídicas e dilemas tecnológicos que surgem do louvável objetivo do legislador da União Europeia de combater conteúdos violentos e terroristas online. O artigo está estruturado da seguinte forma: após uma discussão do conceito fundamental de “conteúdo terrorista” que se aplica de forma geral no texto da minuta (II), distinguimos suas disposições principais que reforçam a conformidade dos provedores de serviços com as ordens para remover ou desativar o acesso ao conteúdo terrorista (III) dos aspectos da proposta que visam responsabilizar os provedores a agir autonomamente contra conteúdo terrorista, inclusive por meio do controverso uso de medidas proativas (IV). Algumas observações finais sobre a direção futura deste arquivo ao vivo são oferecidas na conclusão (V).